Meta-Analysis: Science Learning Based on Local Wisdom Against Preserving School Environments During the Covid-19 Pandemic - Santosa, Tomi Apra; Razak, Abdul; Arsih, Fitri; Sepriyani, Eria Marina; Hernaya, Nita (Journal of Biology Education, 2021)
This study aims to find out science learning based on local wisdom in environmental conservation during the Covid-19 pandemic. This research is a type of meta-analysis research. The sample of this research comes from 30 articles of reputable national and international journals. The data sources were obtained from the google scholar database, Sciencedirect, Wiley of Taylor, IEEE, and Eric. The sampling technique used was purposive sampling technique. The selection of this sample is related to learning science based on local wisdom in environmental conservation efforts. The data analysis technique is the Milles & Huberman model analysis technique which consists of 3 stages, namely reducing data, presenting data, and drawing conclusions. The results showed that science learning based on local wisdom was very good for environmental preservation in Covid-19, the effect size value was 0.923 in the high category.